Infection by Rickettsia felis in Ctenocephalides felis felis Fleas from North of Colombia - Verónica Contreras; Andrés F. Londoño; Jorge Miranda; Salim Mattar; Leidy Y. Acevedo-Gutiérrez; Francisco J. Diaz; Juan D. Rodas (Tehran University of Medical Sciences, 2019)
Background: Rickettsia felis is an emergent Rickettsial agent whose main vector is Ctenocephalides felis, but ticks, mites and lice are also infected. We aimed to search for molecular evidence of Rickettsia spp. in fleas collected from dogs and wild rodents (Heteromys anomalous) from three villages of Córdoba and Antioquia provinces (Northern of Colombia), where outbreaks of rickettsioses have occurred, and discuss the possible role of fleas on endemic/enzootic regions for rickettsia. Methods: During 2010 and 2012, 649 Ctenocephalides felis felis and 24 Pulex irritans fleas were removed from dogs and wild rodents (Heteromys anomalous), respectively, in 3 locations from Córdoba and Antioquia provinces (Colombia). These fleas were tested into pools for Rickettsial infection by PCR, targeting gltA, ompB, and ompA Rickettsial genes. Results: Almost 20% (30/153) of C. felis felis pools contained Rickettsial DNA. The fragments of ompB gene showed high identity values between sequences from Necocli and Los Cordobas with R. felis strain from Senegal (100% and 99.7% respectively) and all were highly related by phylogenetic analyses. Rickettsial DNA in pools of P. irritans was not detected. Conclusion: Our findings highlighted the endemicity of the infection by R. felis in fleas from northern of Colombia and showed the likely importance of dogs as hosts of C. felis felis fleas and their potential role as reservoirs of R. felis.